Early-onset subacute sclerosing panencephalitis and its rapid clinical course of progression to vegetative state: An atypical presentation - Suryawanshi, Vaibhav R; Kalrao, Vijay; Asad, Ali Haider; Tiwary, Pooja; Attarde, Gargi (Indian Journal of Case Reports, 2024)
Subacute sclerosing panencephalitis (SSPE) is a recognized neurodegenerative illness, known to be caused by the persistence of mutated measles virus in neurons and oligodendrocytes. The typical SSPE picture involves behavioral issues followed by myoclonic jerks, progressive intellectual and cognitive decline, bedriddenness, and an incontinent (vegetative) state leading to death. Considering atypicality, ataxia, tremors, dystonia, and hemiparkinsonian features are documented. Very few cases of early-onset SSPE have been reported to date. This report describes one such case with a review of published cases on early-onset SSPE in infants and toddlers in Indian settings. We present the case of a toddler with a positive history of measles at 11 months of age, despite measles vaccination at 9 months, who presented to us 29 months later with repeated head-drops, sudden atonic falls, and recurrent myoclonic jerks. Her brain magnetic resonance imaging and electroencephalography indicated SSPE, which was confirmed by positive antibody titers for measles. The toddler received isoprinosine, anti-seizure medications, and the ketogenic diet, to which she responded well initially. Later, as a consequence, the patient’s clinical condition deteriorated rapidly, and thereby, she attained a complete vegetative state at 3-month follow-up.